The effectivity and flexibility of the legal standard (Società e diritti, 2017)
The positive juridical norms are enacted by the exponential organs of an organized society. They also exist without the social consent from the partners. Every juridical norm must have suited for the concrete case, in how much it is, in its contents and not as commanding, a flexible entity. Besides the right evolves him during the time, and it changes its own juridical configuration. Key words: Juridical norm, Flexibility, Interpretation